Simulation and experimental characterization of gyromagnetic nonlinear transmission lines for prospective aerospace applications - Fernanda Sayuri Yamasaki (Instituto Nacional de Pesquisas Espaciais (INPE), 2017)
A great interest has been devoted to the study of nonlinear transmission lines (NLTLs) for radiofrequency (RF) generation since they have been used with great success in RF generation by producing a train of oscillatory waves along the line and at its output. There are two configurations of NLTLs. The first one is a dispersive line consisting of LC sections with nonlinear components, and the second one is a continuous ferrite loaded non-dispersive line generally biased by an axial magnetic field, known as gyromagnetic line. In this thesis, the focus of the study is on the second one, since gyromagnetic lines can operate in a broader frequency range (0.4 up to 2.0 GHz) with higher conversion efficiency (20.0 %) when compared to lumped NLTLs limited up to 300.0 MHz with less than 10.0 % of efficiency, because of their dielectric losses and stray impedances on line structure. Different models have been used along the years by several authors with different approaches to study the gyromagnetic phenomenon by means of numerical simulations based on analytical models to predict the precession movement of the electron magnetic dipole of the ferrimagnetic material. Thus, the goal of this thesis is to analyze the gyromagnetic NLTL behavior through the effects on the line operation by changing its parameters. The novelty herein is to use Spice simulations based on LC lumped line models to study continuous gyromagnetic NLTLs in addition to numerical simulations usually employed, focusing on the pulse rise time compression and RF generation caused by magnetic dipole precession. Different models are studied by comparing Spice simulations with corresponding results from numerical simulations and experiments found in the literature. Finally, an experimental set-up is described for a 20-cm gyromagnetic line loaded with NiZn ferrite beads to validate with data the proposed method based on Spice simulations. Finally, it is expected that such Spice techniques can be used in the design of these continuous lines for RF applications in space and mobile defense platforms of compact size. === Um grande interesse tem sido dedicado ao estudo de Linhas de Transmissão Não Lineares (LTNLs) para geração de radiofrequência (RF), uma vez que têm sido utilizadas com grande sucesso na geração de RF produzindo um trem de ondas oscilatórias ao longo da linha e em sua saída. Existem duas configurações de LTNLs, a primeira é uma linha dispersiva constituída por seções LC com componentes não lineares, e a segunda é uma linha não dispersiva e contínua, utilizando ferritas geralmente polarizadas por um campo magnético axial, conhecida como giromagnética. Nesta tese, o foco do estudo é na segunda linha, uma vez que ela pode operar em uma faixa de frequência mais ampla (0,4 a 2,0 GHz) com maior eficiência de conversão (20,0 %) quando comparada a LTNLs discreta que é limitada a 300,0 MHz com menos de 10,0 % de eficiência, por causa de suas perdas dielétricas e impedâncias parasitas na estrutura da linha. Diferentes modelos têm sido utilizados ao longo dos anos por vários autores com diferentes abordagens para estudar o fenômeno giromagnético por meio de simulações numéricas baseadas em modelos analíticos para prever o movimento de precessão. Assim, o objetivo desta tese é analisar o comportamento de LTNLs giromagnéticas através dos efeitos na operação da linha mudando seus parâmetros. A novidade aqui é usar simulações Spice com base em modelos de linha LC para estudar as linhas giromagnéticas contínuas, além de simulações numéricas normalmente empregadas, com foco na compressão do tempo de subida de pulso e geração de RF causada pela precessão do campo magnético. Diferentes modelos são estudados comparando-se simulações Spice com resultados correspondentes de simulações numéricas e com experimentos encontrados na literatura. Finalmente, um arranjo experimental para uma linha giromagnética de 20,0 cm usando contas de ferrita NiZn foi implementado para validar com dados experimentais o método proposto baseado em simulações Spice. Finalmente, espera-se que tais técnicas de simulação Spice possam ser usadas na concepção destas linhas contínuas para aplicações de RF no espaço e em plataformas móveis de defesa de tamanho compacto.